Good Governance and Local Wisdom in Law Enforcement - Muhammad Ruhly Kesuma Dinata; Irhammudin Irhammudin; Della Monica; Ruetaitip Chansrakaeo (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2022)
The legal certainty of out-of-court settlements through customary law is still questionable in the Indonesian legal system, even though restorative justice is an approach that aims to build a criminal justice system that is sensitive to the problems of victims. Restorative justice which means a glorification of relationships and making amends that the perpetrator of the crime (his family) wants to make to the victim of the crime outside the court with the intention and purpose that the legal problems arising from the criminal act can be resolved properly by reaching an agreement and agreement between the parties. how is the enforcement of good governance and local wisdom in law enforcement in the North Lampung resort police? This research uses qualitative research methods with a Socio Legal approach. Socio-legal is a legal research approach that uses the help of social sciences as a single approach. Because of this approach, the socio-legal goal is to integrate as a whole the knowledge, skills, and forms of research experience of two (or several) disciplines in an effort to overcome some of the theoretical and methodological limitations of the disciplines concerned. As in the case of Wari Gunawan bin Ngatimin as a suspect for allegedly committing the crime of Fraud Article 378 of the Criminal Code. The result of the research is that in solving problems in the community, the existence of Ippun Aneg is intended as a guideline in handling and/or resolving problems that arise in the community. The settlement of criminal offenses through restoration justice in this case cannot be carried out because the unfinished return of losses received by the victim is the main obstacle to the settlement of this case through restoration justice at the level of investigation and investigation even though peace has been made between the perpetrator and the victim. In addition, the letter of request from the perpetrator, victim and related parties has not been made and submitted, which is an obstacle to the settlement through restoration justice.